PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) TERHADAP PENINGKATAN PEMAHAMAN KONSEP DAN SIKAP ILMIAH PESERTA DIDIK KELAS XI IPA-3 SMA NEGERI 3 AMBON PADA KONSEP LAJU REAKSI - Kadtabalubun, Judith Ekawati; Utubira, Yesliaq (Molluca Journal of Chemistry Education (MJoCE), 2023)
ABSTRACTThis study aims to increase the understanding of the concepts and scientific attitude of class XI IPA-3 students of SMA Negeri 3 Ambon in the reaction rate material through the application of project based learning (PjBL) learning model. This type of research is descriptive quantitative. The study population was the class XI IPA SMA Negeri 3 Ambon and research samples of class XI IPA-3 students numbered 36 students. Data collection uses test and non-test techniques and data analysis is done descriptively by using the again score. The results showed that of the 36 students, 30 students experienced an increase in understanding concepts (83,3%) in the high category and 6 students (16,7%) were in the medium category, with an average n-gain 0,78. Whereas in the scientific attitude at a meeting of I there were 15 students (41,7%) in the very good qualifications, 21 students (58,3%) good qualifications, meeting III 14 students (38,9%) excellent qualifications, 22 students (61,1%) with good qualifications, for enough qualifications and less/failed on the two meetings did not exist.Thus the application of the learning model of the project based learning (PjBL) can improve the understanding of concept and scientific attidude of class XI IPA-3 SMA Negeri 3 Ambon on the concept of reaction rates.